2006
DOI: 10.1245/s10434-006-9055-3
|View full text |Cite
|
Sign up to set email alerts
|

Major Liver Resections Synchronous with Colorectal Surgery

Abstract: Major hepatectomies can be safely performed at the same time as colorectal surgery in selected patients with synchronous metastases with similar short-term results, even in the presence of rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
2
12

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(164 citation statements)
references
References 26 publications
12
138
2
12
Order By: Relevance
“…Liver pedicle clamping can lead to an increased risk of anastomotic leakage because of the onset of intestinal edema (15,16). By laparoscopy, simultaneous resection for RCLM does not require occlusion of the whole hepatic inflow using hemihepatic vascular occlusion (17). Furthermore, the present series provided delayed coloanal anastomosis for patients with middle and low rectal tumor or poor general condition, who have a high prevalence of anastomotic leakage, while avoiding a prophylactic ileostomy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Liver pedicle clamping can lead to an increased risk of anastomotic leakage because of the onset of intestinal edema (15,16). By laparoscopy, simultaneous resection for RCLM does not require occlusion of the whole hepatic inflow using hemihepatic vascular occlusion (17). Furthermore, the present series provided delayed coloanal anastomosis for patients with middle and low rectal tumor or poor general condition, who have a high prevalence of anastomotic leakage, while avoiding a prophylactic ileostomy.…”
Section: Discussionmentioning
confidence: 92%
“…Otherwise, left or right hemi-hepatectomy is another option. Recently, many studies (13,14,17) demonstrated that laparoscopic resection for rectal cancer, combined with synchronous resection of liver metastases, is a safe and feasible procedure in selected patients. With regard to liver metastases that are very difficult to resect with laparoscopy, the simultaneous open operation for liver metastasis is also a good option (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…El índice de resecabilidad global fue de 77,6%, menor que en otras series de nuestro entorno y tal vez por eso, unido a que las intervenciones hepáticas fueron realizadas por el mismo cirujano, la morbilidad global es menor y no hemos tenido complicaciones mayores ni diferencias entre ambos grupos 4,7,12,15,[21][22][23]27,28 (Tabla 3), a pesar de que tenemos 46 pacientes ASA 3, por lo que no creemos que el status preoperatorio deba influir para elegir una u otra estrategia.…”
Section: Supervivenciaunclassified
“…A systematic review of 16 controlled trials showed that the 5-year survival rates in patients with staged and synchronous resections are similar; however, the groups are not directly comparable and there are no randomized data [80]. Synchronous surgery has traditionally been limited to right-sided primaries and those with less extensive hepatic disease, but Capussotti et al [81] challenged this view with a report of safe and effective major hepatectomies for left-sided and rectal tumors. In that study of 79 patients, they found that the overall morbidity rate was higher (56.3% versus 32.6%; p ϭ .0369) and hospital stay was longer (20.5 days versus 13.9 days; p ϭ .00001) in the delayed surgery group when both procedures were considered together.…”
Section: What Is the Optimal Timing Of Liver Resection?mentioning
confidence: 99%